Perception of stakeholders to the proposed ban on cow hide consumption in Ogun State, Nigeria (2016)
The study examined the perception of stakeholders to a ban on cow hide consumption in Ogun State. Purposive and random samplings were used to select 150 respondents. Data was collected using interview schedule and analysed with descriptive and inferential statistics. Results reveal that majority (60.7.0%) of the respondents were female, within the age of 36-42years, married (75.3%) and had secondary education (42.7%). Respondents had low knowledge of the proposed ban (58.0%); 56.0% had high awareness of the possible benefits but 56.0% had negative perception towards the proposed ban. There was significant correlation between sources of information (r=0.279, p=0.001), level of knowledge (r=0.281, p=0.001), constraints that respondents may face from the ban (r=0.165, p=0.043), awareness of the possible benefits (r=0.461, p=0.000) and respondent’s perception to the proposed ban on cow hide consumption. Since more than half of the respondents had negative perception despite their awareness of benefits, concrete efforts need to be taken to improve livestock production in order to cater for leather industries and consumption.